Evidence of Microporous Carbon Nanosheets Showing Fast Kinetics in both Gas Phase and Liquid Phase Environments - Jin, Zhen-Yu; Xu, Yuan-Yuan; Sun, Qiang; Lu, An-Hui (Small (Weinheim an der Bergstrasse, Germany), 2015)
Despite the great advantages of microporous carbons for applications in gas phase separation, liquid phase enrichment, and energy storage devices, direct experiment data and theoretical calculations on the relevance of properties and structures are quite limited. Herein, two model carbon materials are designed and synthesized, i.e., microporous carbon nanosheets (MCN) and microporous carbon spheres (MCS). They both have nearly same composition, surface chemistry, and specific surface area, known morphology, but distinguishable diffusion paths. Based on these two types of materials, a reliable relationship between the morphology with different diffusion paths and adsorption kinetics in both gas phase and liquid phase environments is established. When used for CO2 capture, MCN shows a high saturated CO2 capacity of 8.52 μmol m−2 and 18.4 mmol cm−3 at 273 K and ambient pressure, and its calculated first‐order rate constant is ≈7.4 times higher than that of MCS. Moreover, MCN shows a quick and high uptake of Cr (VI) and a higher‐rate performance for supercapacitors than MCS does. These results strongly confirm that MCN exhibits improved kinetics in gas phase separation, liquid phase enrichment, and energy storage devices due to its shorter diffusion paths and larger exposed geometrical area resulting from the nanosheet structure. Microporous carbon nanosheets and spheres with similar porous structures, specific surface areas, and amorphous features are prepared using the same precursors. Characterizations and application studies indicate that the microporous carbon nanosheets exhibit improve kinetics in gas phase separation, liquid phase enrichment, and energy storage devices, due to their shorter diffusion paths and larger exposed geometrical area derived from the nanosheet structure.